Use of Superior Thyroid Artery as a Donor Vessel in Extracranial-Intracranial Revascularization Procedures: A Novel Technique - Mura, Jorge; Cuevas, José Luis; Riquelme, Francisco; Torche, Esteban; Julio, Rodrigo; Isolan, Gustavo Rassier (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective To describe the use of the superior thyroid artery as a donor vessel in extracranial-intracranial (EC-IC) revascularization when a “low-flow” bypass is required and the superficial temporal artery is not available.Design Case report.Setting University hospital.Participants Four cases.Main Outcome Measures Postoperative course after EC-IC bypass surgery.Results In case 1, the parent vessel was occluded postoperatively. The radial bypass was sufficient to replace the internal carotid artery (ICA) flow, and a prophylactic was turned into a definitive bypass. In case 2, the superior thyroid artery was used because the radial artery was not long enough to reach the external carotid artery. The recipient vessel was modified from the middle cerebral artery to the ophthalmic segment of the ICA. In case 3, the graft was occluded after surgery because of carotid artery reconstruction. In case 4, after surgery/radiotherapy for meningioma, the patient developed wound dehiscence and was reoperated for bypass occlusion. The graft was weak and bled intraoperatively, without infarction. The three first patients are intact, and the fourth remains disabled (Glasgow Outcome Scale: 3; Rankin Scale: 5).Conclusion The superior thyroid artery was adequate for proximal anastomosis in EC-IC procedures in the situations described.
Keywords: cerebral revascularization; EC-IC arterial bypass; brain/blood supply; surgical procedures; operative